Circulating Tumor DNA in Bladder Cancer: Current Clinical Evidence and Emerging Multi-Omics Perspectives—A Narrative Review - Mariam Grazia Polito; Luisana Sisca; Davide Caruso; Antonella Cosimati; Carla Adriana Ramirez Reinaga; Etien Leka; Daniele Santini; Gian Paolo Spinelli (Cancers, 2026)
Background: Circulating tumor DNA (ctDNA) analysis has emerged as a promising tool for real-time disease monitoring in muscle-invasive bladder cancer (MIBC). This narrative review summarizes current clinical evidence regarding ctDNA across disease stages. Methods: We examine recent translational and clinical findings, incorporating key prospective data from practice-changing trials, as well as insights into minimal residual disease (MRD) detection, treatment escalation and de-escalation strategies, and systemic barriers to adoption. Results: Postoperative ctDNA positivity consistently identifies patients with molecular residual disease (MRD) who face a substantially higher risk of recurrence and mortality, frequently preceding radiographic relapse by several months. Prospective evidence now validates ctDNA as a predictive biomarker to guide adjuvant immunotherapy escalation, while sustained ctDNA negativity correlates with high long-term disease-free survival. Beyond plasma ctDNA, emerging multi-compartment liquid biopsies—integrating urinary tumor DNA (utDNA)—demonstrate enhanced sensitivity, particularly in bladder-sparing and local surveillance settings. Furthermore, integrating genomic ctDNA profiling with novel post-transcriptional layers like epitranscriptomics offers a functional framework to capture tumor adaptation under therapeutic pressure. However, clinical translation remains constrained by a lack of assay harmonization, variable analytical sensitivity, and the need for standardized intervention thresholds. Conclusions: Longitudinal liquid biopsies are rapidly shifting MIBC management from static, stage-based paradigms toward dynamic, molecularly informed precision oncology. While ctDNA-guided strategies show robust clinical utility, prospective interventional validation and technical standardization are required before widespread routine integration.